A Wearable Platform for Patient Monitoring during Mass Casualty Incidents - Rodriguez Martinez, Jose David (KIT Scientific Publishing, 2018)
Based on physiological data, intelligent algorithms can assist with the classification and recognition of the most severely impaired victims. This book presents a new sensorbased triage platform with the main proposal to join different sensor and communications technologies into a portable device. This new device must be able to assist the rescue units along with the tactical planning of the operation. This work discusses the implementation and the evaluation of the platform.